Standardization of an in Vitro Regeneration Protocol in Gerbera (Gerbera jamesonii Bolus Ex. Hooker F.) - Koushik Dutta (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2016)
An experiment was undertaken to develop an improved in vitro regeneration protocol in gerbera. Murashige and Skoog (MS) medium was supplemented with various growth regulators at different concentrations for callus induction and organogenesis. Newly emerging leaves of Gerbera cv. Rosalin were used as explants. Experimental results showed that maximum rate (74.07%) of formation of callus with good growth was recorded on MS medium supplemented with 2.0mgL-1 2,4-D + BAP 0.5mgL-1. Best shoot regeneration (57.8 %) with maximum shoot number (12.0) was achieved on with BAP 2.0mgL-1 + NAA 0.5mgL-1 fortified MS medium. Maximum (66.7 %) and earliest (12.3 days) root formation in shoots was recorded on IBA 3.0mgL-1is 1/2MS media. Survival rate of regenerated plantlets was maximum (73.33 %) in the potting mixture containing garden soil, sand and vermicompost (1:1:1).